2009
DOI: 10.1002/eji.200838729
|View full text |Cite
|
Sign up to set email alerts
|

BM stromal cells ameliorate experimental autoimmune myasthenia gravis by altering the balance of Th cells through the secretion of IDO

Abstract: In addition to their capacity to differentiate, BM stromal cells (BMSC) have immunosuppressive qualities that make them strong candidates for use in cell therapy against human autoimmune diseases. We studied the immunoregulatory activities of BMSC on experimental autoimmune myasthenia gravis (EAMG) in vitro and in vivo. Intravenous administration of syngenic BMSC to EAMG-model rats on the day of their second immunization was effective in ameliorating the pathological features of the disease. In vitro, the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Also, the proliferative response of T cells in response to AChR stimulation was increased when stimulated by IL-17 in vitro [64e66]. Moreover, treatment with immunosuppressive bone marrow stromal cells or dendritic cells ameliorated EAMG symptoms by shifting the balance from Th1/Th17 dominance towards Th2/Treg dominance [65,66]. A similar balance between regulatory and inflammatory T cells was also observed in a clinical study, in which MG patients with reduced Treg cells showed more severe MG symptoms [67].…”
Section: Th1/th17 Versus Th2-type Immunitymentioning
confidence: 99%
“…Also, the proliferative response of T cells in response to AChR stimulation was increased when stimulated by IL-17 in vitro [64e66]. Moreover, treatment with immunosuppressive bone marrow stromal cells or dendritic cells ameliorated EAMG symptoms by shifting the balance from Th1/Th17 dominance towards Th2/Treg dominance [65,66]. A similar balance between regulatory and inflammatory T cells was also observed in a clinical study, in which MG patients with reduced Treg cells showed more severe MG symptoms [67].…”
Section: Th1/th17 Versus Th2-type Immunitymentioning
confidence: 99%
“…The low immunogenicity and immunomodulatory effects of MSCs have been well reported. [8][9][10][11][12][13][14][15][16] Ouyang et al reported no apparent lymphocyte infiltration with the use of allogeneic BMSCs for tendon repair, 17,18 although the number of labeled stem cells decreased with time; and the authors suggested that this was related to the tendon remodeling process. 18 No identification of inflammatory cells was done in these previous studies.…”
Section: Introductionmentioning
confidence: 94%
“…Both tryptophan depletion and the presence of its metabolite kynurenine are able to suppress T-cell proliferation [21,22]. Moreover, IDO is also considered to be involved in the generation of regulatory T cells and tolerogenic dendritic cells induced by MSCs [23][24][25]. MSCs do not constitutively express IDO, but interferon-γ (IFN-γ) induces IDO expression in a dose-dependent manner [18].…”
Section: Introductionmentioning
confidence: 99%